2019
DOI: 10.1016/j.addr.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles for personalized medicine: The input of physically triggered production, loading and theranostic properties

Abstract: Emerging advances in extracellular vesicle (EV) research brings along new promises for tailoring clinical treatments in order to meet specific disease features of each patient in a personalized medicine concept. EVs may act as regenerative effectors conveying endogenous therapeutic factors from parent cells or constitute a bio-camouflaged delivery system for exogenous therapeutic agents. Physical stimulation may be an important tool in the field of EVs for personalized therapy by powering EV production, loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 153 publications
3
81
0
5
Order By: Relevance
“…EVs are of great interest and importance in drug delivery. The promising advantages of low immunogenicity, intrinsic cell targeting properties, and enhanced stability in circulation make them more and more attractive in targeted drug therapy (Liao et al, 2019;Piffoux et al, 2019). They have been revealed huge potentials in the therapy of various diseases including malignancies and neurology diseases (Bunggulawa et al, 2018;Khan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…EVs are of great interest and importance in drug delivery. The promising advantages of low immunogenicity, intrinsic cell targeting properties, and enhanced stability in circulation make them more and more attractive in targeted drug therapy (Liao et al, 2019;Piffoux et al, 2019). They have been revealed huge potentials in the therapy of various diseases including malignancies and neurology diseases (Bunggulawa et al, 2018;Khan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In general, EVs are classified into three major groups: exosomes, microvesicles and apoptotic bodies based on vesicle diameter and the release process (26). Exosomes are the smallest vesicles (~ 50 -100 nm) released through exocytosis of endosomal multivesicular bodies.…”
mentioning
confidence: 99%
“…It has been reported that MSC culture and EV production in hypoxic conditions (1–5% O 2 ) increase the number of EVs released and their cargo composition (growth factors and miRNAs), thus enhancing their pro-angiogenic, immunomodulatory, cardioprotective and neuroprotective effects ( Cui et al, 2018 ; Xue et al, 2018 ; Zhu et al, 2018 ). Another option is to take advantage of bioreactors to mechanically stimulate EV production by applying fluid shear stress or compression [for review, see Piffoux et al (2019) ]. Although, the underlying mechanisms are not known, one hypothesis is that in this condition, MSCs inhibit their own re-uptake of EVs.…”
Section: Challenges For the Industrial Production Of Gmp-grade Extracmentioning
confidence: 99%